Caracterização de carotenoides e atividade antioxidante da biomassa microalgal - Patias, Luciana Dapieve (2017)
This study has the folloing objectives: (i) to identify the carotenoid profile of these three species of microalgae: Chlorella vulgaris, Scenedesmus obliquus and Aphanotece microscopica Nägeli; (ii) to quantify the carotenoids of those three microalgae species; (iii) to evaluate the antioxidant activity of carotenoid extracts obtained from microalgal biomasses; (iv) to identify the carotenoid profile of the microalga extract with the highest antioxidant potential at different culture times and (v) to quantify the carotenoids of the microalgae extracts with higher antioxidant potential at different culture times. The obtained results have showed that the three species of microalgae have presented the capacity to produce a significant carotenoid content under photoautotrophic conditions, indicating their potential as a renewable source of these pigments. These extracts have proved to be a potent peroxil radical scavenger. The highest antioxidant activity has been noticed in the microalgae Chlorella vulgaris, favored by its carotenoid profile, which contains a large number of conjugated double bonds. It is important to emphasize that this has been the first research related to the carotenoid profile and the Scenedesmus obliquus and Aphanotece microscopica Nägeli antioxidant capacity. The study has also showed that the cultivation time may be important to define in which phase one can accumulate specific carotenoids, and predict the performance and the optimization of operating conditions. The results achieved from this study in the sense that microalgae must be considered a potential feedstock to a great diversity of natural carotenoids production.